P173 The role of transcutaneous carbon dioxide monitoring in acute non-invasive ventilation. (14th November 2013) - Oppen, J Van; Daniel, P; Sovani, M
Abstract : Background: Transcutaneous carbon dioxide monitoring is rarely used in the acute hospital setting, where samples of arterial blood are used to measure pCO2. This is a pilot observational study to assess the role of transcutaneous (ptc CO2 ) versus arterial (pa CO2 ) monitoring during acute NIV, both to calculate pH and to guide therapy. Methods: Ten patients with acute hypercapnic respiratory failure were recruited. All had arterial lines placed for guiding acute NIV therapy. ptc CO2 was monitored for 12 hours (Radiometer TOSCA TCM4) and compared to measures of pa CO2 from samples taken from the arterial lines. Non-invasive pHtc was calculated from ptc CO2 . Agreements between pCO2 and pH methods were assessed using Bland-Altman analysis and regression. The potential for guiding acute NIV therapy based on transcutaneous data was assessed and pain scores for each method were compared using the Wilcoxon signed rank test. Results: Mean bias between pa CO2 and ptc CO2 was -0.31 (95% CI 0.98) kPa, R 2 = 0.79 (p < 0.0001). ptc CO2 followed the same time trend as pa CO2 . Mean pH bias was not statistically significant at 0.006 (95% CI 0.116), R 2 = 0.64 (p < 0.0001). If based on transcutaneous data only, clinical decisions would have been unchanged in nine out of ten patients. Transcutaneous readings were also less painful (p < 0.001) and preferred by patients. Conclusion: This pilot study demonstrates the potential for using transcutaneous pCO2 monitoring to calculate pH and guide therapy, in the acute care setting. ptc CO2 shows promise in replacing arterial blood gases, in acute hypercapnic respiratory failure.